KERAGAAN AGROINDUSTRI KERUPUK UDANG DI KECAMATAN KWANYAR KABUPATEN BANGKALAN - Hastinawati, Ika; Rum, Mokh. (Program Studi Agribisnis Fakultas Pertanian Universitas Trunojoyo Madura., 2012)
This research was conducted in the village of West Kwanyar, Kwanyar District, Bangkalan. The purpose of this study was to determine the performance and financial feasibility of agro-industries of prawn cracker. The sampling method in this study use a purposive technique that is implemented in the West Kwanyar Village, Kwanyar District. The analysis used was a qualitative descriptive analysis to determine the performance profile agro prawn crackers, while the agro-industry analysis of the financial feasibility of prawn crackers use quantitative descriptive analysis is the calculation of BEP, R/C ratio and ROI. The technique of data collected by through observation, questionnaires, interviews, literature study and documentation. Based on research result shows that the performance profile of agro-industrial scale prawn crackers is a household that is using the loan capital as initial capital to start a business, yet have a business license so that the market is still in the vicinity of Sub Kwanyar by using two channels, the first manufacturer to distributor and then to the consumer and finally manufacturer to market directly to consumers. Is financially feasible to develop agro-industry that is obtained from the calculation of cost and revenue analysis, analysis of BEP (Break Even Point), R/C Ratio (Revenue Cost Ratio) and ROI (Return on Investment).